Functional response properties of VIP-expressing inhibitory neurons in mouse visual and auditory cortex - Mesik, Lukas; Ma, Wen-pei; Li, Ling-yun; Ibrahim, Leena A.; Huang, Z. J.; Zhang, Li I.; Tao, Huizhong W. (Frontiers in Neural Circuits, 2015)
Despite accounting for about 20% of all the layer 2/3 inhibitory interneurons, the vasoactive intestinal polypeptide (VIP) expressing neurons remain the least thoroughly studied of the major inhibitory subtypes. In recent studies, VIP neurons have been shown to be activated by a variety of cortico-cortical and neuromodulatory inputs, but their basic sensory response properties remain poorly characterized. We set out to explore the functional properties of layer 2/3 VIP neurons in the primary visual (V1) and primary auditory cortex (A1), using two-photon imaging guided patch recordings. We found that in the V1, VIP neurons were generally broadly tuned, with their sensory response properties resembling those of parvalbumin (PV) expressing neurons. With the exception of response latency, they did not exhibit a significant difference from PV neurons across any of the properties tested, including overlap index, response modulation, orientation selectivity and direction selectivity. In the A1, on the other hand, VIP neurons had a strong tendency to be intensity selective, which is a property associated with a subset of putative pyramidal cells and virtually absent in PV neurons. VIP neurons had a best intensity that was significantly lower than that of PV and putative pyramidal neurons.Finally, sensory evoked spike responses of VIP neurons were delayed relative to pyramidal and PV neurons in both the V1 and A1. Combined, these results demonstrate that the sensory response properties of VIP neurons do not fit a simple model of being either PV-like broadly tuned or pyramidal-like narrowly tuned. Instead, the selectivity pattern varies with sensory area and can even be, as in the case of low sound intensity responsiveness, distinct from both PV and pyramidal neurons.